2012
DOI: 10.2214/ajr.11.7664
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Filter–Associated Abnormalities: MDCT Findings

Abstract: In this review, we discuss the various pathologic abnormalities related to inferior vena cava filters, as seen on MDCT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Hence, the rate of complications due to indwelling filters may be significantly higher than that currently reported (►Table 2). 32,33 While complications may occur at any point following implantation, the majority occur following prolonged implantation, and indeed a systematic review by Angel et al 34 confirmed that the vast majority (93%) of complications with retrievable IVC filters occurred with long-term use (>30 days). Furthermore, the success of retrieval attempts has been shown to decrease with prolonged dwell times.…”
Section: Inferior Vena Cava Filter Retrieval Evidence For Removalmentioning
confidence: 99%
“…Hence, the rate of complications due to indwelling filters may be significantly higher than that currently reported (►Table 2). 32,33 While complications may occur at any point following implantation, the majority occur following prolonged implantation, and indeed a systematic review by Angel et al 34 confirmed that the vast majority (93%) of complications with retrievable IVC filters occurred with long-term use (>30 days). Furthermore, the success of retrieval attempts has been shown to decrease with prolonged dwell times.…”
Section: Inferior Vena Cava Filter Retrieval Evidence For Removalmentioning
confidence: 99%
“…13 and 14 ). CTV is preferred when assessing potential inferior vena cava (IVC) filter complications, such as malposition, migration, tilting, caval thrombosis or perforation [ 117 ].
Fig.
…”
Section: Notes On Specific Protocolsmentioning
confidence: 99%
“…In descending order, the most common sites for filter fragment embolization were pulmonary arteries (31%), iliac/femoral veins (27%), and the right ventricle and renal vein (3.8% each) [146]. Factors that increase the risk of filter migration and embolization include the so-called "mega-IVC" (e.g., IVC diameter ≥28mm), filter malpositioning, and a large embolus creating a "sail effect" that then dislodges the filter from the IVC, with subsequent embolization to the heart [147][148][149]. A fracture-free survival model described by Tam et al, predicted a fracture rate of 40% at 5.5 years [146].…”
Section: Ivc Filter Migration and Embolizationmentioning
confidence: 99%